Pola Alih Tutur (Turn-Taking) dalam Interaksi Kelas: Analisis Percakapan pada Perkuliahan Keterampilan Berbahasa Jerman - Iman santoso, - (2020)
Turn-taking in a talk-in interaction is a key factor that ensures the process of exchanging roles between the speaker and the speech partner runs smoothly. This applies to all natural and institutional conversations. Thus far, most research on turn-taking has focused on natural conversational interactions. However, it appears that there is still not much research on turn-taking in conversational interactions in the context of foreign language learning. Therefore, this research was conducted to examine the turn-taking that occurred in lecturing German language skills as a foreign language. This study aims to discover: (1) turn-taking patterns realized in German language skills lectures, (2) the contribution of structural elements of conversation to turn-taking realization, (3) factors that have the potential to influence turn-taking realization. This research was conducted using a descriptive qualitative research design. The speech analysis paradigm based on the theory of Sacks et al., (1974) was used as an analytical tool. The data analysis unit in this study was speech transfer in conversational interactions between lecturers and students in German language skills lectures. Data collection was carried out by using a recording technique at four German language skills lecture meetings at a university in the Special Region of Yogyakarta. The recordings were then transcribed using Jefferson's (2004) notation. The Data were analyzed over the speech that appeared along with the structural elements of the conversation and the factors that influenced its realizations. The results of this study indicate that: (1) the most widely realized turn-taking is self-select to be a speaker, followed by the current-speaker being selected by the previous speaker and the current-speaker continuing his turn. This study shows that the patterns of turn-taking in German language skills are different from the patterns of turn-taking in natural conversations; (2) the structural elements of conversation that contribute to the realization of speech transfer are gaps and overlaps that are not minimized. Repairs of turns occurred in the form of self-initiated self-repair constituted participants' preferences. The form of adjacency pairs that is most often realized is the question - answer. Meanwhile, the majority of adjacency pairs have the second part which is preferred; (3) the allocation of speech transfer by the participants was driven by a variety of factors, namely repair, procedural factors related to the learning process, explanation, reinforcement of student responses, evaluation of student understanding, transfer of topics, understanding of the lecturers' speech, giving responses and asking questions from students. In this study, turn-taking patterns that occurs in conversational interactions in lecturing German language skills can be formulated.